The Role of Site Variance in the American Judicature Society Field Study Comparing Simultaneous and Sequential Lineups - Amendola, Karen L. (Journal of quantitative criminology, 2017)
Objectives Police departments often use photo lineups for eyewitness identification purposes. A widely adopted lineup reform designed to reduce eyewitness misidentifications involves switching from the standard simultaneous photo presentation format to a sequential format. These two lineup procedures were recently tested in the American Judicature Society (AJS) field study, which was conducted in four different police jurisdictions. The results from two phases of that investigation reached opposite conclusions as to which lineup procedure is superior, and the purpose of our current investigation was to elucidate the role of site variance in shaping those contrasting conclusions. Methods In previous analyses, the field study data were either (1) aggregated across all four study sites or (2) drawn from only one study site (Austin, Texas). Here, we analyze the data separately for the Austin study site, where 69 % of the eyewitnesses were tested, and the other three study sites combined, where 31 % of the eyewitnesses were tested. Results The results indicate significant site variance between the Austin and non-Austin study sites. In addition, the results suggest that aggregating the data across sites played a determinative role in creating the apparent disagreement about which lineup procedure is diagnostically superior. Conclusions Once large differences across the AJS study sites are taken into consideration, there is no longer any disagreement about which lineup procedure is superior. The simultaneous procedure is diagnostically superior to the sequential procedure, but the sequential procedure sometimes induces more conservative responding (a result that can and often does masquerade as diagnostic superiority).